1996
DOI: 10.1021/ie950399d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Stability, and Sulfation Properties of Sol−Gel-Derived Regenerative Sorbents for Flue Gas Desulfurization

Abstract: The sol-gel method is applied to prepare γ-alumina-supported copper oxide and calcium oxide sorbents containing 10-50 wt % active species. The prepared sorbents are characterized for their pore texture, dispersion of active species on the surface of support, and desulfurization properties. The sol-gel-derived alumina-supported sorbents have a relatively large surface area (>200 m 2 /g) and pore volume (>0.3 cm 3 /g) and uniform pore size distribution (20-60 Å). Thermal and chemical stability of the sol-gel-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
(42 reference statements)
4
28
0
Order By: Relevance
“…The decrease is more obvious as the total weight percent increases from 40% to 90%. This finding is similar to that by Deng and Lin, 7 whose active species have a much smaller surface area. Such decrease in the surface area will lead to a sharp decrease in the adsorption capacity to be shown later.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The decrease is more obvious as the total weight percent increases from 40% to 90%. This finding is similar to that by Deng and Lin, 7 whose active species have a much smaller surface area. Such decrease in the surface area will lead to a sharp decrease in the adsorption capacity to be shown later.…”
Section: Resultssupporting
confidence: 90%
“…7,8 The preparation process of metal adsorbents is similar to that of metal catalysts, which requires high activity, sensitivity, and stability. The widely used preparation methods for metal catalysts are described with their merits and demerits by Pinna.…”
Section: Introductionmentioning
confidence: 99%
“…Various CuO content in -Al2O3 were reported by previous researchers [6][7][8][9][10]. The effective CuO content on -Al2O3 was in the range of 4-8 % by mass [1,5,11], though more CuO could be impregnated [1,6,8,11]. Increasing CuO of course increase the sulfur loading of adsorbent CuO/-Al2O3.…”
Section: Introductionmentioning
confidence: 89%
“…According to the monolayer loading theory, copper supported on alumina was observed to be present not as crystalline CuO or CuAl 2 O 4 but as a less well-defined entity for roughly a monolayer coverage. 15 For copper loadings in excess of monolayer coverage of sorbent with CuO, crystalline CuO appears on the surface. 15 This indicated that the loading amount of CuO (<10 wt %) had dispersed well on the internal pore surface of the alumina support by the wetting impregnation method used here.…”
Section: Methodsmentioning
confidence: 99%
“…15 For copper loadings in excess of monolayer coverage of sorbent with CuO, crystalline CuO appears on the surface. 15 This indicated that the loading amount of CuO (<10 wt %) had dispersed well on the internal pore surface of the alumina support by the wetting impregnation method used here. Excessive CuO crystallized and was present on the external surface of the particles.…”
Section: Methodsmentioning
confidence: 99%